Influence of an inspiratory muscle fatigue protocol on older adults on respiratory muscle strength and heart rate variability. A randomized controlled trial - Ladriñán-Maestro, Arturo; Sánchez-Infante, Jorge; Martín-Vera, Daniel; Del-Blanco-Muñiz, José Ángel; Merino-Andrés, Javier; Sánchez-Sierra, Alberto (Frontiers in Neuroscience, 2024)
IntroductionInspiratory muscle fatigue has been shown to have effects on the autonomic nervous system and physical condition. This study aimed to evaluate the influence of an inspiratory muscle fatigue protocol on respiratory muscle strength and heart rate variability in older adults.Materials and methodsA randomized controlled clinical trial with double-blinding was carried out involving 24 individuals over 60 years old who demonstrated physical independence in walking and movement. Participants were distributed randomly into three groups: Inspiratory muscle fatigue, activation and control. Measurements of heart rate variability, diaphragmatic ultrasound, and maximum inspiratory pressure were taken at two stages: prior to the intervention (T1) and directly after treatment (T2).ResultsThe inspiratory muscle fatigue group exhibited decrease scores in respiratory and heart rate variability subsequent to undergoing the diaphragmatic fatigue intervention compared to both the activation and control groups (p < 0.05). Conversely, the activation group demonstrated higher values in heart rate variability and respiratory capacity variables following the inspiratory muscle activation training (p < 0.05).ConclusionsFatigue of the inspiratory musculature appears to negatively impact heart rate variability and inspiratory muscle strength in older adults.Clinical trial registrationhttps://clinicaltrials.gov/study/NCT06269042, identifier: NCT06269042.